Pengolahan Limbah Cair Tahu Menggunakan Kombinasi Serbuk Kelor (Moringa oleifera) dan Asam Jawa (Tamarindus indica) - Mukarlina, Robin Januardi, Tri Rima Setyawati (Jurnal Protobiont, 2014)
Tofu industrial wastewater containing high protein causes highly suspended solids (TSS) and dissolved solids (TDS). Moringa oleifera and Tamarindus indica seed powder can be used as a coagulant to reduce TSS and TDS. This study aims to determine best dose and the effectiveness of the combination Moringa and Tamarind seeds in improving the quality tofu liquid waste. The research was conducted in Pebruary to April 2013. Value TSS, TDS and total bacteria before treatment at high 1232 mg/l, 8432 mg/l and 2,7107 CFU/ml. The best treatment was at the dose K2:A1 (Moringa 133,3 mg and Tamarind 66,7 mg) with the final value TSS 151 mg/l, while the final value TDS 2794 mg/l. Best treatment for the total bacteria was at the dose K1:A2 (Moringa 66,7 mg and Tamarind 133,3 mg) with the final value 3,1106 CFU/ml. Once the tofu liquid waste is treated, the mean value of dissolved oxygen was 3,09 to 3,67 ppm and the degree of acidity was 4,67 to 5,00.